1991
DOI: 10.1136/bmj.302.6780.833
|View full text |Cite
|
Sign up to set email alerts
|

Can health education increase uptake of cervical smear testing among Asian women?

Abstract: Objectives-To determine the effects of three different methods of providing health education on the uptake of cervical smear testing among Asian women, and to evaluate the acceptability of different health education materials.Design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 17 publications
0
60
0
1
Order By: Relevance
“…In the UK, Asian women from the Indian sub-continent have low rates of cervical screening. 37 In summary, despite sampling differences between the National Health Surveys, and in the absence of data on ethnicity on the Pap test register, this study provides information on time trends in Pap test rates among migrant groups and cross-sectional differences in Pap testing in the previous three years. To achieve high participation rates in cervical screening, it is important to recruit all women regardless of their ethnicity.…”
Section: Taylor Et Al Articlementioning
confidence: 95%
“…In the UK, Asian women from the Indian sub-continent have low rates of cervical screening. 37 In summary, despite sampling differences between the National Health Surveys, and in the absence of data on ethnicity on the Pap test register, this study provides information on time trends in Pap test rates among migrant groups and cross-sectional differences in Pap testing in the previous three years. To achieve high participation rates in cervical screening, it is important to recruit all women regardless of their ethnicity.…”
Section: Taylor Et Al Articlementioning
confidence: 95%
“…Some studies have previously evaluated the effectiveness of various strategies (Hisamichi et al, 1991;Watanabe, 2003;Shimada et al, 2010a;Shimada et al, 2010b;Matsuda et al, 2011;Takaku, 2011;Kuroki, 2012;Yoshida et al, 2012), but it was difficult to compare the effectiveness of these strategies, as each study focused on the effectiveness of an individual strategy using different subjects and methodologies. As the most effective strategy in improving cancer screening rates differs depending on the country and region (McAvoy and Raza, 1991;King et al, 1994;Saywell et al, 1999;Champion et al, 2003;Saywell et al, 2003;Saywell et al, 2004;Blumenthal at al., 2010;Lee et al, 2012;Frie et al, 2013), it remains unclear which strategy would be the most effective in Japan. Therefore, a study comparing the effectiveness of different strategies used to improve cancer screening rates in Japan is warranted and poised to be very useful for decision makers.…”
Section: What Is the Most Effective Strategy For Improving The Cancermentioning
confidence: 99%
“…The UK literature reports only one trial for cervical cancer screening; this found that home visits were more effective than a postal leaflet, with some evidence that home viewed videos may be particularly effective in one of the most hard to reach groups, Urdu speaking Pakistani Moslems. 71 Slightly more UK trials of interventions to improve breast cancer screening uptake have been reported. Based on these, it would seem that the use of a reminder letter has only a limited role in improving uptake.…”
Section: Cervical and Breast Cancer Screeningmentioning
confidence: 99%